1985
DOI: 10.1177/028418518502600201
|View full text |Cite
|
Sign up to set email alerts
|

Angiography of the Internal Mammary Artery

Abstract: The anatomy and catheterization techniques of the internal mammary artery (i.m.a.) are described. The diagnostic criteria and importance of i.m.a. angiography in thymoma, lymphoma, carcinoma, parathyroid adenoma, diseases of the breast, and trauma are discussed. The role of i.m.a. catheterization for i.a. infusion therapy in lung carcinoma, mesothelioma and chest wall metastases of breast carcinoma and embolization of i.m.a. in bleeding following trauma or tumour ulceration are described. Transcatheter treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…21 In fact, classic anatomic studies have demonstrated that in the entire adult human spinal cord, only 3 to 10 anterior, and 10 to 24 posterior RAs remain. lO RAs arise from subclavian artery branches, aortic ICAs, and lumbar arteries and are necessary for spinal cord viability.1O, 12,13 The largest RA, the arteria radicularis magnus, originates between T9 and T12 75% of the time. 4 ,14,22,23 This vessel is a necessary though not sufficient supply for the spinal cord 24 because it preferentially directs flow distally in the anterior spinal artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In fact, classic anatomic studies have demonstrated that in the entire adult human spinal cord, only 3 to 10 anterior, and 10 to 24 posterior RAs remain. lO RAs arise from subclavian artery branches, aortic ICAs, and lumbar arteries and are necessary for spinal cord viability.1O, 12,13 The largest RA, the arteria radicularis magnus, originates between T9 and T12 75% of the time. 4 ,14,22,23 This vessel is a necessary though not sufficient supply for the spinal cord 24 because it preferentially directs flow distally in the anterior spinal artery.…”
Section: Discussionmentioning
confidence: 99%
“…4 ,5 Anatomic and angiographic studies have clearly demonstrated that the internal mammary arteries (!MAs) supply the anterior intercostal arteries (ICAs) and connect with the posterior ICAs arising from the aorta. 12 , 13 The posterior ICAs then supply the thoracic spinal cord via radicular arteries (RA) ( Fig. 1) .…”
mentioning
confidence: 99%
“…In case of arterial bleeding, there are several ways to manage the hemorrhage: selective angiographic embolization, US-guided hemostatic injection, and conservative management, such as compression [94]. When there's no injury of the great vessels, MDCT angiography often allows to detect bleeding from branches of the internal mammary artery, which can be embolized successfully with low complication rates [95].…”
Section: Treatmentmentioning
confidence: 99%
“…The IMA terminates into two end arteries, specifically the musculophrenic artery, which provides anastomotic branches to the lower posterior intercostal arteries, and the superior epigastric artery, which anastomoses with the inferior epigastric artery. [18][19][20] Injury to the IMA can occur as a result of blunt or penetrating trauma to the chest. Iatrogenic damage to the IMA is possible during anterior chest wall procedures, such as wire closure after median sternotomy.…”
Section: Internal Mammary Arterymentioning
confidence: 99%